2021
DOI: 10.7150/thno.53624
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic miR-378 modulates serum cholesterol levels by regulating hepatic bile acid synthesis

Abstract: Rationale: An improved understanding of thyroid hormone (TH) action on cholesterol metabolism will facilitate the identification of novel therapeutic targets for hypercholesterolemia. TH-regulated microRNAs (miRNAs) have been implicated in TH-controlled biological processes; however, whether and how TH-regulated miRNAs mediate the cholesterol-lowering effect of TH remains unclear. Our aim was to identify TH-regulated microRNAs that have cholesterol-lowering effects and explore the underlying mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…SOAT2 is essential for converting cholesterol into cholesterol ester (CE), and the latter is the preferred form of LDL ( 85 ); and TH mediated the reduction of miR-206, so TG and TC in HepG2 cells declined ( 86 ). Also, TH could positively regulate hepatic miR-378, leading to the reduction of serum cholesterol levels through promoting bile acid synthetic pathways ( 87 ). Recently, a regulatory module containing three miRNAs (miR-34a-5p, miR-24-3p and miR-130a-3p) and four proteins (thioredoxin, selenium-binding protein 2, elongation factor 1β and prosaposin) about hepatic lipid metabolism was identified in subclinical mice ( 88 ).…”
Section: The Mechanism Of Dyslipidemia In Hypothyroidismmentioning
confidence: 99%
“…SOAT2 is essential for converting cholesterol into cholesterol ester (CE), and the latter is the preferred form of LDL ( 85 ); and TH mediated the reduction of miR-206, so TG and TC in HepG2 cells declined ( 86 ). Also, TH could positively regulate hepatic miR-378, leading to the reduction of serum cholesterol levels through promoting bile acid synthetic pathways ( 87 ). Recently, a regulatory module containing three miRNAs (miR-34a-5p, miR-24-3p and miR-130a-3p) and four proteins (thioredoxin, selenium-binding protein 2, elongation factor 1β and prosaposin) about hepatic lipid metabolism was identified in subclinical mice ( 88 ).…”
Section: The Mechanism Of Dyslipidemia In Hypothyroidismmentioning
confidence: 99%
“…Nine miRNAs were involved in the ceRNA interactions, but none of them showed associations with testicular development. Sun et al [ 60 ] report that the mice lacking miR-378 have defects in cholesterol homeostasis. In this study, the expression level of cholesterol side-chain cleavage enzyme (CYP11A1) increased from 8.62 FPKM to 52.33 FPKM, so we assumed that differentially expressed miR-378 might provide conditions for the following spermatogenesis by maintaining cholesterol homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-378 has been implicated in regulating osteogenic differentiation and follicle development [ 41 ]. Studies have also shown that miR-378 can modulate cholesterol levels, suppress hepatoma cell growth, and induce apoptosis in cancer cells [ 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%